METHYLMALONIC ACID AND HOMOCYSTEIN SERUM IN DIAGNOSING MEGALOBLASTIC ANEMIA DUE TO COBALAMIN AND FOLATE DEFICIENCY IN TRAVEL MEDICINE - Indra Rahayuda, Made Gian; Herawati, Sianny (E-Jurnal Medika Udayana, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Anemia is a major global health problem, especially in developing countries. Anemia is a condition where the red blood cell mass and / or hemoglobin mass that circulating in the body was decreased to below normal level so it can not function well in providing oxygen to the body tissues . One of the most common type is megaloblastic anemia. Megaloblastic anemia is mostly caused by vitamin B 12 (cobalamin) and folate deficiency. One of the causes of cobalamin and folate deficiency anemia is tropical sprue. Cobalamin deficiency anemia and folate deficiency anemia gives a similar symptom, but in cobalamin deficiency there is neuropathy symptoms. Normal serum folate is between 3-15 ng/mL. Normal folate erythrocyte is 150-600 ng/mL. In cobalamin deficiency, serum cobalamin decreased below the cut off point 100pg/mL (normally 100 - 400pg/mL). Other examination such as elevated homocysteine ?? , methylmalonic acid, or formioglutamic acid (FIGLU) in the urine can confirm the diagnosis of cobalamin and folic acid deficiency. There is no consensus on the cut-off point of homocysteine ?? and MMA. Homocysteine ?? has been considered to increase when the levels are above 12-14 ?mol /L in women and in the 14-15 ?mol/L. According to research by Robert et al in the case of cobalamin deficiency, serum tHcy> 15.0 ?mol/L. Most research considers the increase of MMA in cobalamin deficiency is> 0:28 ?mol / L, but the cut off point in circulation varies between 0:21 to 0:48 ?mol/L. MMA level is increased in serum and urine in cobalamin deficiency, whereas MMA normal in folate deficiency. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Anemia, Megaloblastic Anemia, Cobalamin, Folate, Tropical Sprue, Homocystein, Metylmalonic Acid.